Dampak peluang dan kemampuan untuk mengubah sikap terhadap lingkungan menjadi perilaku konsumen yang Pro-Lingkungan - Manik, Yuni Mariani; Wahjoedi, Wahjoedi; Wahyono, Hari; Sumarsono, Hadi (Jurnal Ekonomi Modernisasi, 2023)
Even though there is customer concern and positive attitudes towards sustainability and environmentally friendly products, the market share of these products is still limited to 1–3 percent of the total market. The phenomenon in which consumers' positive attitudes toward the environment are incongruent with their purchasing behavior of environmentally friendly products is known as “eco-friendly attitude-behavior gap.” This research aims to explain the reasons behind the persistence of this gap and to determine whether moderator variables, such as ability and opportunity, can reduce the gap. The survey was conducted on 355 students as consumers in Bandar Lampung City using a framework adopted from different literature. The research results show that affordability plays an important role in encouraging consumers to make more environmentally friendly purchases, especially when accompanied by knowledge of eco labels. However, opportunity is not a moderating influencing factor. This article reaches its conclusion by presenting strategies that can be implemented by practicing managers who wish to expand the market for environmentally friendly products. Two moderating variables, namely ability and opportunity, were generated from the Motivation-Ability-Opportunity (MAO) model to understand the relationship between attitudes towards the environment and consumer behavior that supports the environment, especially in the context of developing countries such as Indonesia.